Hubungan Tingkat Pendidikan, Pengetahuan dan Dukungan Keluarga dengan Asupan Protein Pasien Gagal Ginjal Kronik (GGK) yang Menjalani Hemodialisa (HD) Rawat Jalan Di RSUD Sukoharjo - Sitaga, Sri; , Ririn Yuliati S.Si.T., M.Si; , Tuti Rahmawati, S.Gz.,M.Si (2015)
Introduction: The level of education, knowledge and family support affect protein intake hemodialysis patients with chronic kidney disease. Protein intake is important for hemodialysis patients with chronic kidney disease need to maintain nitrogen balance and replace amino acids lost during dialysis. Objective: To analyze the relationship between the level of education, knowledge and familysupport with intake in patients with chronic kidney disease undergoing hemodialysis out patients in Sukoharjo General hospital. Methods: an observational study with cross sectional approach with 31 people of samples. The sample was chronic kidney disease patients with 18-60 years of age. Data collected using questionnaires and FFQ form, were analyzed using Pearson Product Moment Correlation test. Results: Most respondent have primary education (74.19%), 58.06% of respondents have a good knowledge, 58.06% of respondents have a good family support, 66.66% of respondents have excessiveprotein . Results of statistical test analysis between protein intake level and education wasp = 0.29, between knowledge and protein intake was p = 0.43, while family support and protein intake was p = 0.49. Conclusion: There is no relationship between the level of education, knowledge and family supportwith the protein intake in patients with chronic kidney disease undergoing hemodialysis outpatients in Sukoharjo District hospitals. Suggestions: improve cooperational relationship between nutrition counseling clinic in the diet of hemodialysis chronic kidney disease order, so patients can prevent complications which caused by the intake they consumed.